The Effect of Physical-Psychological and Psychological Stress on Blood Glucose Levels (In vivo Study) - Agustin Wulan Suci Dharmayanti; Erfin Ramadana Pratama; Banun Kusumawardani; Zahreni Hamzah; Suhartini Suhartini; Tecky Indriana; Dwi Warna Aju Fatmawati (Universitas Muhammadiyah Yogyakarta, 2023)
Stress is a condition that burdens a person and affects homeostasis resulting in health problems, including dental and oral health. Stress can be caused by physical, chemical, or psychological stressors. Stressors cause an increase in blood glucose levels due to an increase in the stress hormone cortisol. This study aims to determine the effect of physical-psychological and psychological stress induced by electrical foot shock on blood glucose levels in rats. This research is an experimental laboratory study with a post-test control group design using white male rats as animal stress models. Animal models were divided into six groups, namely physical-psychological stress for 7 days (PPS1), 14 days (PPS2), and 28 days (PPS3); and psychological stress for 7 days (PS1), 14 days (PS2), and 28 days (PS3). The animal models were placed in the experimental box with electrical foot shock. The physical-psychological stress treatment was to flow an electric current of 48 V, 0.5 Hz, 2 mA for 30 minutes daily. In the psychological stress treatment, the animal models were placed without an electric shock, but the animal models were placed together, given an electric shock stressor separated by transparent plastic with a thickness of 5 cm and foam at the bottom of the cage (insulator). The results showed that although there was no effect of electrical foot shock on blood glucose levels in rats experiencing physical-psychological stress for 7, 14, and 28 exposures (p0.05), electrical foot shock affected blood glucose levels in rats with psychological stress (p0.05). It can be concluded that physical-psychological and psychological stress induced by electrical foot shock affected blood glucose levels.